An improved low-voltage ride-through performance of DFIG based wind plant using stator dynamic composite fault current limiter. (May 2016) - Gayen, P.K.; Chatterjee, D.; Goswami, S.K.
Abstract: In this paper, an enhanced low-voltage ride-through (LVRT) performance of a grid connected doubly fed induction generator (DFIG) has been presented with the usage of stator dynamic composite fault current limiter (SDCFCL). This protection circuit comprises of a suitable series resistor–inductor combination and parallel bidirectional semiconductor switch. The SDCFCL facilitates double benefits such as reduction of rotor induced open circuit voltage due to increased value of stator total inductance and concurrent increase of rotor impedance. Both effects will limit rotor circuit over current and over voltage situation more secured way in comparison to the conventional scheme like the dynamic rotor current limiter (RCL) during any type of fault situation. The proposed concept is validated through the simulation study of the grid integrated 2.0 MW DFIG. Highlights: An improved protection circuit SDCFCL is proposed for DFIG. LVRT performance is substantially improved under any kind of fault condition. LVRT capability with SDCFCL is superior to conventional rotor current limiter. SDCFCL helps to handle more fundamental current component by RSC during fault. The LVRT control loop for controlling RSC does not involve any flux computation.